Mechanisms of physical and biochemical basis of resistance against leaf-hopper (Amrasca biguttula biguttula) in different okra (Abelmoschus esculentus) genotypes - HALDER, JAYDEEP; SANWAL, S K; DEB, DIBYENDU; RAI, A B; SINGH, B (The Indian Journal of Agricultural Sciences, 2016)
Different biophysical parameters, viz. trichomes, leaf length, angle between the mid-ribs, angle between the midribs and vein, mid-rib thickness, leaf angle, number of leaves/plant, plant height and biochemical parameter like total phenol content of leaves were studied in relation to the expression of reaction towards leaf hopper (Amrasca biguttula biguttula) in 10 okra [Abelmoschus esculentus (L.) Moench] genotypes. It was observed that genotype SB-6 had relatively lower number of trichomes on leaf lamina (10.11), mid-rib (7.17) and vein (8.05) as showed highly susceptible to jassids (17.57 jassids/leaf) as compared to tolerant genotype VROB-181 (5.43 jassids/leaf) which had 11.85, 9.17 and 9.95 trichomes per cm2, respectively. Susceptible cultivar SB-10 possessed higher mid-rib thickness (1.75 mm) and leaf length (25.65 cm) as compared to tolerant genotype VROB-181 (1.58 mm and 22.43 cm, respectively). Similarly, higher number of total leaves (31.9) per plant was also recorded from SB-6 as compared to other tolerant lines (VROB-181, VROB-178, VROR-160). Leaf length, plant height, angle between mid-ribs and total leaves showed a strong positive correlation (r value = 0.493, 0.499, 0.723 and 0.474, respectively) with jassid incidence. Amongst the biochemical parameter, total phenol content was highest in VROB-181 (75.04 mg/100 g) and the incidence of jassids was lowest than those of susceptible genotypes, viz. SB-6 (42.61 mg/100 g) and SB-10 (48.35 mg/100 g) and thereby establishing the significant negative correlation (r = - 0.577) with the jassid incidence and total phenol content.